Coping with COVID-19 stressors: A study with university level students - Mollika Roy; Saira Hossain (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Abstract: COVID-19 outbreak caused a global crisis in every possible sector. More specifically, the health, economy, and education sectors. Different initiatives have been taken to mitigate the global crisis, such as movement restriction, Movement Control Order (MCO), and social distancing for a long time. Consequently, all educational institutions across the globe had to remain closed for a long time. They limited the scope of face-to-face classes and grossly jeopardised students' social lives. Students had to face several unforeseen challenges worldwide for which they were unprepared. In this study, we mainly investigated the stressors students faced due to COVID-19 and how this has cost their coping strategies. We recruited 228 university students (Undergrad, postgrad, and PhD). Among them, 50% were undergraduate students. We found anxiety regarding family safety, timely completion of the degree and study level as the most common COVID-19-related stressors. Besides these, cognitive restructuring and social support were the two most commonly used coping strategies to handle students' stress during the pandemic. We recommend taking the initiative to accelerate positive coping strategies among students to cope with real-life crises more effectively.Keywords: COVID 19; coping strategies; stressors; and university studentsAbstrak: Wabah COVID-19 menyebabkan krisis global di segala bidang. Lebih khusus lagi, sektor kesehatan, ekonomi, dan pendidikan. Berbagai inisiatif telah diambil untuk memitigasi krisis global, seperti pembatasan pergerakan, Movement Control Order (MCO), dan jarak sosial untuk waktu yang lama. Akibatnya, semua institusi pendidikan di seluruh dunia harus ditutup untuk waktu yang lama. Mereka membatasi ruang lingkup kelas tatap muka dan sangat membahayakan kehidupan sosial siswa. Siswa harus menghadapi beberapa tantangan tidak terduga di seluruh dunia yang tidak mereka siapkan. Dalam studi ini, kami terutama menyelidiki stresor yang dihadapi siswa akibat COVID-19 dan bagaimana hal ini merugikan strategi koping mereka. Subjek penelitian ini 228 mahasiswa (Sarjana, Pascasarjana, dan PhD). Di antara mereka, 50% adalah mahasiswa sarjana. Kami menemukan kecemasan terkait keamanan keluarga, penyelesaian gelar, dan tingkat studi tepat waktu sebagai pemicu stres terkait COVID-19 yang paling umum. Selain itu, restrukturisasi kognitif dan dukungan sosial merupakan dua strategi koping yang paling banyak digunakan untuk mengatasi stres mahasiswa selama pandemi. Kami merekomendasikan mengambil inisiatif untuk mempercepat strategi koping positif di kalangan siswa untuk mengatasi krisis kehidupan nyata secara lebih efektif.Kata kunci: COVID 19; strategi penanggulangan; penyebab stres; dan mahasiswa